Penerapan Pembelajaran Sentra Bahan Alam Dalam Mengoptimalkan Kemandirian Anak Usia 4 – 5 Tahun: Sentra Bahan Alam, Kemandirian Anak Usia Dini - Dwi Sekarningtyas Sekar Tyas; Sudarti; Diana (Jurnal Kajian Anak (J-Sanak), 2024)
The point of this inquire about is to depict the arranging, execution, appraisal and impediments in executing common materials center learning in optimizing the autonomous capacities of children matured 4 – 5 TK Mujahidin Kindergarten 1. The investigate comes about appear that: 1) The arranging carried out by the educator some time recently the learning prepare starts, such as making instructing modules concurring to the autonomous educational programs that will be utilized, by counting points, subtopics, subtopics, learning goals, learning steps, evaluation plans and learning assets. 2) Usage carried out by the educator in learning such as planning, steps some time recently playing, steps amid play and steps after playing. 3) Evaluations carried out by instructors at school utilize perception sheets and recounted notes for each day of learning exercises. 4) Deterrents experienced by instructors within the handle of actualizing normal materials center learning in optimizing children`s free capacities such as trouble in conditioning children when learning exercises take put so that the classroom atmosphere gets to be ineffectual.